Konsep Perkembangan Kognitif Perspektif Al-Ghazali Dan Jean Piaget - AD, Yahya (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
The equation of cognitive development (reason) according to Al-Ghazali and Jean Piaget is found at the stages of development which are divided into four stages. In addition, the views of the two figures also have a relationship or meeting point found in the aspects of the ability of each stage that is passed in each process of cognitive development (reason). Differences in cognitive development (reason) according to Al-Ghazali and Jean Piaget are found in the methodology as the basis of both thoughts. the research method used is a philosophical comparative method, so the systematic discussion follows the following patterns or stages: 1) describes the concept of each character, 2) displays each concept, then compares it, 3) looks for and finds distinctive characteristics, including the similarities and differences of each of the two thoughts, and 4) conducting a critical evaluation of these two thoughts. Al-Ghazali based his thinking on ratios derived from revelation while Jean Piaget laid his rationale on pure ratios. In addition, there are also differences in the views of both of them in the use of the term, Al-Ghazali uses the term sense while Jean Piaget uses the term cognitive.